PELAKSANAAN KEGIATAN EKSTRAKURIKULER PADUAN SUARA DI SMP NEGERI 26 PADANG - Arman Soni; Irdhan Epria Darma Putra; erfan erfan (FBS Universitas Negeri Padang, 2018)
Abstract This article aims to describe the implementation of extracurricular activities the choir to cultivate interest in Junior High School students in the country 26 field. This type of research is a qualitative descriptive method of analysis. The object of this research is the coach of the extracurricular choirs in 26 Country Junior High School field. The technique of data collection was done through observation, interviews, and the study of the literature. The analysis is done via data classification, description, and analysis, as well as a summary. The research results showed that the implementation of extracurricular choirs in 26 228 Padang still have not gone well and have yet to fully use the perfect rehearsal stage. Even so, the motivation given coach against the students can create a sense of optimism and spirit of the student in following this process so that the implementation of extracurricular activities extracurricular choirs can continue running. Keywords: extracurricular activities, choir